The effects of klapskate hinge position on push-off performance: a simulation study - Houdijk, H.; Bobbert, M. F.; de Koning, J. J.; de Groot, G. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: The introduction of the klapskate in speed skating confronts skaters with the question of how to adjust the position of the hinge in order to maximize performance. The purpose of this study was to reveal the constraint that klapskate hinge position imposes on push-off performance in speed skating. METHOD: For this purpose, a model of the musculoskeletal system was designed to simulate a simplified, two-dimensional skating push off. To capture the essence of a skating push off, this model performed a one-leg vertical jump, from a frictionless surface, while keeping its trunk horizontally. In this model, klapskate hinge position was varied by varying the length of the foot segment between 115 and 300 mm. With each foot length, an optimal control solution was found that resulted in the maximal amount of vertical kinetic and potential energy of the body's center of mass at take off (Weff). RESULTS: Foot length was shown to considerably affect push-off performance. Maximal Weff was obtained with a foot length of 185 mm and decreased by approximately 25% at either foot length of 115 mm and 300 mm. The reason for this decrease was that foot length affected the onset and control of foot rotation. This resulted in a distortion of the pattern of leg segment rotations and affected muscle work (Wmus) and the efficacy ratio (Weff/Wmus) of the entire leg system. CONCLUSION: Despite its simplicity, the model very well described and explained the effects of klapskate hinge position on push off performance that have been observed in speed-skating experiments. The simplicity of the model, however, does not allow quantitative analyses of optimal klapskate hinge position for speed-skating practice.